Healthcare personnel vaccination policies in michigan long-term care facilities. (20th June 2018) - Kimmins, Lynsey M.; Bramer, Cristi A.; Chandler, Jacklyn L.; Hart, Adam L.
Abstract: Of the 461 licensed long-term care facilities (LTCFs) in Michigan, 129 responded to the first survey of LTCF healthcare personnel (HCP) immunization policies, coverage estimates, and perceived barriers to vaccination. Survey results suggest opportunities to improve HCP vaccination through polices, education, barrier removal, and HCP immunity status tracking in licensed LTCFs in Michigan.